2010
DOI: 10.1007/s10344-010-0392-y
|View full text |Cite
|
Sign up to set email alerts
|

An audio/video surveillance system for wildlife

Abstract: We report 7 years of experience with an inexpensive and reliable continuous audio/video recording system. The main components of the system are commercial, infrared illuminator surveillance cameras, mini microphones and portable digital video recorders, powered by deep cycle leadacid batteries. We used the system for monitoring 41 broods of four endemic bird species in tropical rainforests of New Caledonia. We recorded for over 22,000 h in total. We kept the system at nests for a maximum period of 7 months, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…Knight et al (2014) (Pallas, 1764). These evidences, and our data suggest that camera systems based on motion sensors rarely achieve 100% efficiency in the detection of predators, as occurs, for example, with most devices with full time recording (time-lapse devices) (Sabine et al 2005, Pierce and Pobprasert 2007, Gula et al 2010, Kirkpatrick and Conway 2010, Smith et al 2012, Denmon et al 2013.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Knight et al (2014) (Pallas, 1764). These evidences, and our data suggest that camera systems based on motion sensors rarely achieve 100% efficiency in the detection of predators, as occurs, for example, with most devices with full time recording (time-lapse devices) (Sabine et al 2005, Pierce and Pobprasert 2007, Gula et al 2010, Kirkpatrick and Conway 2010, Smith et al 2012, Denmon et al 2013.…”
Section: Discussionmentioning
confidence: 91%
“…However, the primary limitation of most devices is the requirement of separate parts, e.g. cameras, batteries, and motion sensors, that are difficult to carry and to set up in the field (Pierce and Pobprasert 2007, Sabine et al 2005, Grivas et al 2009, Gula et al 2010, Smith et al 2012, Denmon et al 2013. Digital video cameras that are currently available commercially (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Under ideal breeding conditions, this means that the female parakeet will rarely need to leave the nest to forage as most of the food is supplied by the male partner, or by multiple partners (Theuerkauf et al 2009). Aside from any nutritional advantage this provides, reproductive success may improve because Black Rats (Rattus rattus) rarely prey upon eggs or chicks in a nest that is guarded by the female (Gula et al 2010). However, food availability alone may not completely explain the selection of oligotrophic soils.…”
Section: Discussionmentioning
confidence: 99%
“…a significant difference between predator and prey population sizes (2000 pairs of redtailed tropicbirds vs. more than 100,000 rats), stomach content analysis cannot be considered as a suitable method. Video surveillance showed that rats often visited nests of red-tailed tropicbirds, more than reported elsewhere (Gula et al, 2010). These visits occurred especially when the chicks were left alone by their parents.…”
mentioning
confidence: 88%